2003
DOI: 10.1007/s00027-003-0666-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental flooding on brown trout (Salmo trutta fario L.): The River Sp�l, Swiss National Park

Abstract: Following the construction of two large reservoirs in the late 1960s on the River Spöl, Swiss National Park, flow was greatly reduced and regulated at a relatively constant discharge. The regulated flow regime resulted in the elimination of river changing floods, causing altered and degraded habitat conditions for the brown trout (Salmo trutta fario L.). Although food resources (i.e., zoobenthos abundance) increased after flow regulation, trout spawning areas were greatly reduced by the clogging of coarse sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 18 publications
4
49
0
Order By: Relevance
“…Trout can die because of physical injury caused by substrate movement, or after being stranded in remnant pools on the riverbed or floodplain (Jowett 1997;Ortlepp and Murle 2003). Another potential mechanism of mortality, suggested by our study, may be burial by largescale substrate movement, although we cannot be sure whether the fish located beneath substrate and debris following the flood were dead before burial.…”
Section: Flood-induced Mortalitymentioning
confidence: 77%
See 3 more Smart Citations
“…Trout can die because of physical injury caused by substrate movement, or after being stranded in remnant pools on the riverbed or floodplain (Jowett 1997;Ortlepp and Murle 2003). Another potential mechanism of mortality, suggested by our study, may be burial by largescale substrate movement, although we cannot be sure whether the fish located beneath substrate and debris following the flood were dead before burial.…”
Section: Flood-induced Mortalitymentioning
confidence: 77%
“…Trout may also be swept downstream or out to sea. Some studies have indicated that fish displaced downstream by floods have returned upstream during the flood recession (Dedual and Jowett 1999;Dare et al 2002;Ortlepp and Murle 2003). As far as we are aware, there are few direct observations of trout mortality resulting NOTE from floods (but see Ortlepp and Murle 2003).…”
Section: Flood-induced Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…After hatching, young alevin remain in the gravel until the yolk sac is used up and they emerge as 'fry' from the gravel. In case of severe riverbed clogging before spawning, eggs are either not spawned (Ortlepp and Murle 2003;Mathisen 1955in DeVries 1997 or insufficiently covered by gravel, with an increased risk for wash out with high floods (Everest et al 1987in DeVries 1997. As fines are usually transported downstream by currents during redd construction, the initial percentage of fines in the redd is often reported to be lower (e.g.…”
Section: Habitat Requirements Of Gravel-spawning Brown Troutmentioning
confidence: 99%